The impact of DRG payment reform on inpatient costs for different surgery types: an empirical analysis based on Chinese tertiary hospitals - Luo, Mingwei; Li, Hongying; Li, Rongyue; Wu, Yugao; Lan, Yuping; Xie, Shiwei (Frontiers in Public Health, 2025)
BackgroundTo evaluate the impact of DRG (Diagnosis-Related Group) payment reform on inpatient costs for four major types of surgery at a tertiary hospital in China, with a focus on its implementation in general surgery, cardiothoracic surgery, neurosurgery, and urology.MethodsBased on inpatient data from 2019 to 2023, the study employed Propensity Score Matching (PSM) and Difference-in-Differences (DiD) models to compare inpatient cost differences between the DRG payment group and the non-DRG payment group. Concentration indices were used to assess the consistency of inpatient cost distribution.ResultsThe DRG payment reform significantly reduced the total inpatient costs for surgeries in general surgery, cardiothoracic surgery, neurosurgery, and urology, particularly in terms of drug and material expenses. Additionally, the inpatient cost distribution in the DRG payment group became more concentrated, indicating a significant reduction in the proportion of high-cost cases.ConclusionThe DRG payment reform effectively controlled inpatient costs in Chinese tertiary hospitals, particularly for complex surgical procedures, and improved the efficiency of healthcare resource utilization. This study provides empirical support for the further implementation of DRG payment reform and offers policy recommendations for optimizing China’s healthcare payment system.